Lumbar Intraspinal Osteolipoma Presenting as Cauda Equina Syndrome: A Case Report and Review of Literature - S. Dilip Chand Raja; Rishi Mugesh Kanna; Ajoy Prasad Shetty; S. Rajasekaran (Case Reports in Orthopedics)
Introduction. Osteolipomas are uncommon variants of lipoma. These lesions have been usually reported to arise from the oral cavity, brain, and neck and scarcely from the knee and thigh. Intraspinal osteolipomas are rare. A single case of intraspinal osteolipoma has been reported in the cervical and thoracic spine in the literature. To our knowledge, there is no report of osteolipomas in the lumbar spine. Case Presentation. We report a very rare case of a solitary lumbar intraspinal osteolipoma, presenting as a cauda equina syndrome. The intraspinal osteolipoma was excised en bloc and fusion was performed as it required partial resection of the facet joint within 24 hours of presentation. He has since then improved neurologically, and there has been no recurrence of the lesion so far. The clinical presentation, radiological characteristics, treatment course, and histopathological features of this lesion along with the clinical outcomes and a pertinent literature review were done and have been discussed. Discussion. The heterogeneous signal intensity of the lesion in MRI differentiates it from other dural-based lesions, and this should raise suspicion of an osteolipoma, which warrants a CT. Although intraspinal osteolipomas are benign lesions and generally have good prognosis, they need to be removed en bloc as they may result in rapid neurological deterioration.